Desafíos en la formación de ciudadanía en los estudiantes de décimo año de educación general básica y tercero de bachillerato en el colegio Cardenal Spellman - Bravo Hidalgo, Marianela Jacqueline (2017)
The topic of this degree work is: Challenges in the citizenship training with the students of tenth year of general basic education and third year of bachillerato in Pichincha province, Quito city Cumbaya parish, commune Lumbisí at Cardenal Spellman High- School. This institution is addressed from a socio-educational perspective in which the existent relationship between students and teachers in observed from the educational context and at the same time, without omitting, the family context that is very important. In this process, opinions about the family context are integrated. Furthermore, it involves the understanding in how the Salesiano context involves every single opinion and the impact they have when including Christian values in the school environment. From the quantitative point of view, it presents an analysis of results which emphasizes in the probable assimilation of de students about their natural and social environments, not only as individuals but also as a whole society that changes continuously and asks for results in a production way which allows to become an active part of a radical transformation on our social surroundings. From the qualitative sight, it has been checked student’s strengths who in the moment of the investigation were an active part in the learning role for they got educated as opinion individuals and not only as spectators of a society full of challenges in the social politics. Finally, this research work is firstly structured with the contextualization in the educational institution, immediately conceptual theoretical frame is explained which will permit giving favorable responded to the solution of our problem.